Nano Comes to Life : How Nanotechnology Is Transforming Medicine and the Future of Biology - Contera, Sonia (Princeton University Press, 2019)
The nanotechnology revolution that will transform human health and longevityNano Comes to Life opens a window onto the nanoscale-the infinitesimal realm of proteins and DNA where physics and cellular and molecular biology meet-and introduces readers to the rapidly evolving nanotechnologies that are allowing us to manipulate the very building blocks of life. Sonia Contera gives an insider's perspective on this new frontier, revealing how nanotechnology enables a new kind of multidisciplinary science that is poised to give us control over our own biology, our health, and our lives.Drawing on her perspective as one of today's leading researchers in the field, Contera describes the exciting ways in which nanotechnology makes it possible to understand, interact with, and manipulate biology-such as by designing and building artificial structures and even machines at the nanoscale using DNA, proteins, and other biological molecules as materials. In turn, nanotechnology is revolutionizing medicine in ways that will have profound effects on our health and longevity, from nanoscale machines that can target individual cancer cells and deliver drugs more effectively, to nanoantibiotics that can fight resistant bacteria, to the engineering of tissues and organs for research, drug discovery, and transplantation.The future will bring about the continued fusion of nanotechnology with biology, physics, medicine, and cutting-edge fields like robotics and artificial intelligence, ushering us into a new "transmaterial era." As we contemplate the power, advantages, and risks of accessing and manipulating our own biology, Contera offers insight and hope that we may all share in the benefits of this revolutionary research.